Особенности семенной репродукции луковичных и клубнелуковичных эфемероидных геофитов мировой флоры, интродуцированных на юго-востоке Украины - Павлова, М.А. (Промышленная ботаника, 2013)
Наведено результати аналізу даних, отриманих при сівбі насіння цибулинних та бульбоцибулинних геофітів світової флори у Донецькому ботанічному саду НАН України, проведеній у різні строки і за різних умов у період з 1995 до 2005 рр. На основі аналізу розроблений оптимальний спосіб насіннєвого розмноження представників цієї екобіоморфи в умовах степової зони південного сходу України, диференційований залежно від ценотичної приуроченості інтродуцентів. In this study, the data on sowing seeds of bulbous and tuber-bulbous ephemeroid geophytes of the world flora in the Donetsk Botanical Garden of the National Academy of Sciences of Ukraine are analyzed. The seeds have being sown in 1995–2005 in different terms and conditions. Based on this analysis, we have developed an optimal method of seed propagation for the representatives of this ecological biomorph in steppe conditions of the southeast of Ukraine. This method is differentiated with regard of the cenotic confinement of introduced plants.